CHILDHOOD - AS A SOCIO-PHILOSOPHICAL PROBLEM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the perfection of man and the level of spiritual and moralvalues as the basis that determines the development of society, and draws attention to the humanproblem, the socialization of childhood. The article reveals opinions on the formation of personality in rare works of great eastern thinkers: Abu Nasr Farabi, A. Navoi and Z.M. Babura.
Keywords: childhood, personality formation, teacher responsibility, “soft” or “hard” methods, determination of behavior, meaningful childhood, Islamic philosophy, life needs, theoretical maturity, thirst for knowledge.